ISLAM AND HOMO DEUS IN ANTHROPOCENTRIC THEOLOGY: A RELIGIOUS CHALLENGE IN THE FUTURE - Maulida, Syazna; Ja'far, Suhermanto (TAJDID: Jurnal Ilmu Ushuluddin, 2022)
This article discusses Islam and Homo Deus in anthropocentric theology. As for the background of the research this is that in the 21st century humanity logically hopes that the spirit Homo Deus will lead them to put more effort into searching for meaning real life. Meanwhile, Artificial Intelligence technology (artificial intelligence) is currently preferred and is even believed to be able to undermine spiritual intelligence human beings, thereby weakening human efforts in finding meaning in life and solving social problems in their environment, such as caring for social change, ignorance, poverty and underdevelopment.The method used in this article is a qualitative method library (study library). Sources of data obtained from the results of literature studies that limited to matters that have relevance to this study. Findings in this research is that modern technology gives mankind most likely obtained a tremendous increase in material life but does not mean at the same time providing a means for improving the quality of humanity. Thus in the future the role of religion will be even greater, especially religion which is seen in its totality, as a way of life, as a giver of meaning to life. Religious teachings such as Islam which should be a guide for its adherents become very important in providing ethical guidance to humans, including in the ethics of the development and use of science and technology. Islam with spiritual teachings, exercises in reviving the human conscience, its absolute values ​​as contained in the Qur'an and Hadith mutawatir, the teachings of humanism, the position of reason which is high in Islam, so that it can lead to a rational interpretation is religion that can meet the needs of mankind in modern times.   Artikel ini mendiskusikan tentang Islam dan Homo Deus dalam teologi antroposentris. Adapun yang menjadi latar belakang penelitian ini adalah bahwa pada abad 21 secara logis umat manusia berharap bahwa semangat Homo Deus akan membawa mereka untuk lebih berupaya dalam mencari makna kehidupan yang sebenarnya. Sementara itu, teknologi Artificial Intelligence (kecerdasan buatan) saat ini lebih diutamakan bahkan diyakini dapat menggerogoti kecerdasan spiritual manusia sehingga melemahkan ikhtiar manusia dalam mencari makna kehidupan dan memecahkan masalah-masalah sosial, seperti peduli terhadap perubahan sosial, kebodohan, kemiskinan dan keterbelakangan. Adapun metode yang digunakan dalam artikel ini adalah metode kualitatif kepustakaan (library research). Sumber data yang diperoleh dari hasil studi literature yang dibatasi dengan hal-hal yang memiliki relevansi dengan penelitian ini. Hasil temuan dalam penelitian ini adalah bahwa teknologi modern memberi umat manusia kemungkinan besar memperoleh peningkatan hidup material yang luar biasa namun tidak berarti juga sekaligus menyediakan sarana bagi peningkatan kualitas kemanusiaan. Demikian dimasa depan peran agama akan semakin besar khususnya agama yang dilihat secara totalitas, sebagai jalan hidup, sebagai pemberi makna kehidupan. Ajaran agama seperti Islam yang seharusnya menjadi pedoman untuk penganutnya menjadi sangat penting dalam memberikan bimbingan etika pada manusia termasuk dalam etika pengembangan dan pemanfaatan ilmu pengetahuan dan teknologi. Islam dengan ajaran kerohanian latihan-latihan dalam menghidupkan nurani manusia, nilai-nilainya yang absolut sebagaimana yang terdapat pada al-Qur‘an dan hadis mutawatir, ajaran humanisme, kedudukan akal yang tinggi dalam Islam, sehingga dapat menimbulkan penafsiran rasional adalah agama yang dapat memenuhi kebutuhan umat manusia di zaman modern.